PENGGUNAAN METODE TPR (TOTAL PHYSICAL RESPONSE) SEBAGAI UPAYAMENINGKATKAN KETERAMPILAN BERBICARA BAHASA INGGRIS SISWA KELAS V SDN SAMIRONO YOGYAKARTA - Dewi Masitoh, Maria Wulandari, dan Retno Kurniasari Widianingsih (Pelita - Jurnal Penelitian Mahasiswa UNY, 2011)
The research was aimed at improving the English speaking skills of the grade V students of SDN SamironoYogyakarta. This research focused on the implementation of TPR method to improve the students’ speaking skills.This research was a classroom action research. The subjects of the research were 19 students. The researchwas conducted in two cycles. Each cycle was divided into four steps, i.e. planning, observing, acting, and reflecting.The data were collected through interviews, observations, field notes and documentations. The data were analyzedby using a qualitative descriptive technique. The success of the research was achieved based on the criteria of thelevel of speaking confidence, ability to understand the teacher’s instructions, understanding of the lesson materials,and ability to pronounce words accurately. The improvement can be seen through the scoring rubrics with therange of 1 to 5. Level 1 indicated extremely poor quality; level 2 indicated poor quality; level 3 indicated adequatequality; level 4 indicated good quality; and level 5 indicated very good quality.The level of speaking confidence increased from level 3 in the first cycle to level 4 in the second level. Theability to understand the teacher’s instructions and learning materials was still in level 4 in both cycles. The abilityto pronounce words accurately was still in level 2 in both cycles.Keywords: Total Physical Response (TPR), speaking skills, grade V students